AN ANALYSIS OF LEXICAL DENSITY ON READING MATERIALS IN ENGLISH INTERLANGUAGE TEXTBOOK FOR THE TENTH-GRADE SENIOR HIGH SCHOOL - Sabuna, Vicky Petra Kurnia; Bunau, Eusabinus; Wardah, Wardah (STKIP Persada Khatulistiwa Sintang, 2024)
Reading is one of the important language skills students have to master. Some forms of reading materials are written in English, to mention some are books, articles, and textbooks. English Interlanguage Textbook for the Tenth-Grade Senior High School was one of the reading materials chosen as the focus of this research. In terms of the content of the textbook, the teacher should be able to decide whether it is informative or not. The objectives of this study were (1) to find out the lexical density of the reading materials in the English Interlanguage textbook, and (2) to describe the lexical density of the reading materials in the English Interlanguage Textbook. In this study, the researcher chose qualitative research as the methodology. The data collected from the textbook showed that there were 9 reading materials that were categorized into different kinds of text. Those were narrative text, recount text, descriptive text, and news item text. The lexical density of reading material in the English Interlanguage Textbook for the tenth-grade of Senior High School was around 40% - 60%. It infers that the lexical density was sufficient. Also, the reading materials were clear, understandable, and suitable for students.Keywords: Descriptive research, lexical density, textbook analysis